ChemInform Abstract: Task‐Specific Design of Porous Polymer Heterogeneous Catalysts Beyond Homogeneous Counterparts. Issue 39 (September 2015) - Sun, Qi; Dai, Zhifeng; Meng, Xiangju; Wang, Liang; Xiao, Feng‐Shou
Abstract Review: 89 refs.